A Data Set of Final Year High School Examination Texts of South African Home and First Additional Language Subjects - Sibeko, Johannes; van Zaanen, Menno (Journal of open humanities data, 2023)
This article describes a data set of reading comprehension and summary writing texts that were used in final-year high school examinations in South Africa between 2008 and 2020. It contains texts for eleven official South African languages. PDF versions of the texts stem from South Africa’s Department of Basic Education’s online public access repository. Plain text is extracted from the PDFs and the texts are tokenized. The data set contains 429 full-text files with 929 manually extracted comprehension and summary writing texts. The data is useful for studies investigating, e.g., linguistic properties, text readability, text properties, and linguistic complexity in any of the eleven languages. Furthermore, both intra-language and inter-language comparisons or investigations can be made.